Serological diagnosis of Staphylococcus aureus osteomyelitis. - Wheat, L J (1985)
We have evaluated serological tests for the diagnosis of Staphylococcus aureus osteomyelitis. Antiteichoic acid antibodies were elevated in 17 of 23 patients with acute and 16 of 46 with chronic S. aureus osteomyelitis but in none of 33 patients infected with other gram-positive or gram-negative bacteria. Immunoglobulin G antibodies to S. aureus were elevated in 12 of 23 patients with acute and 22 of 47 with chronic S. aureus osteomyelitis, in 2 of 12 infected with other gram-positive bacteria, and in 4 of 21 with other gram-negative bacteria. Assays for S. aureus antibodies may be useful for identifying patients with S. aureus bacteremia complicated by metastatic sites of infection in bone and for identifying the etiological agents in patients with negative or mixed cultures or from whom cultures are not readily available. Prospective studies are needed to test these hypotheses.